2019
DOI: 10.1021/acs.jpcc.9b02329
|View full text |Cite
|
Sign up to set email alerts
|

Patterning the Internal Structure of Single Crystals by Gel Incorporation

Abstract: Single crystals are usually homogeneous, whereas heterogeneous internal structures can be constructed by incorporation of foreign materials. The existence of the homogeneous and heterogeneous states (termed as state “0” and “1”) inspires the idea to transform crystals between them so that the internal structures in the crystals become patternable. Here, gel-grown potassium dihydrogen phosphate single crystals transforming between “0” and “1” states (without and with gel incorporation) are demonstrated by oscil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(33 citation statements)
references
References 44 publications
1
32
0
Order By: Relevance
“…Interaction between the inorganic matrix and the organic inclusions (usually peptides or polysaccharides) in biominerals is complex and is not yet fully understood. [ 55,56 ] Calcite, the most thermodynamically stable polymorph of CaCO 3, [ 57 ] was nevertheless shown to be capable of incorporating proteins, [ 56,58 ] polymer nanoparticles, [ 59,60 ] dyes, [ 61 ] inorganic nanoparticles, [ 62–64 ] graphene oxide, [ 65 ] anticancer drugs, [ 66 ] gels, [ 67,68 ] and individual amino acids. [ 69–71 ] Incorporation of amino acids induces expansion of the unit cell (i.e., an increase of the lattice parameters, both a and c ), and is accompanied by significant changes in the crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Interaction between the inorganic matrix and the organic inclusions (usually peptides or polysaccharides) in biominerals is complex and is not yet fully understood. [ 55,56 ] Calcite, the most thermodynamically stable polymorph of CaCO 3, [ 57 ] was nevertheless shown to be capable of incorporating proteins, [ 56,58 ] polymer nanoparticles, [ 59,60 ] dyes, [ 61 ] inorganic nanoparticles, [ 62–64 ] graphene oxide, [ 65 ] anticancer drugs, [ 66 ] gels, [ 67,68 ] and individual amino acids. [ 69–71 ] Incorporation of amino acids induces expansion of the unit cell (i.e., an increase of the lattice parameters, both a and c ), and is accompanied by significant changes in the crystal morphology.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Li and co‐workers have demonstrated that crystallization within a gel can be used to design the internal structure of potassium dihydrogen phosphate single crystals. By changing the crystallization conditions of growth rate between slow and fast modes or by oscillating the crystallization medium between solutions and gels, patterned internal structures either with or without incorporated gel networks can be obtained . Having established a deeper understanding of surface‐confined occlusion, we sought to control nanoparticle occlusion within the growing calcite crystals to produce patterned regions.…”
Section: Resultsmentioning
confidence: 99%
“…22 Copyright 2016, American Chemical Society. OM, optical microscopy; SAED, selected area electron diffraction incorporation, where the incorporated species only distributed throughout the center region (core) of a singlecrystal with a guest-free shell layer, was found in either particles 73 or gel networks 28 incorporation. The probable forming mechanisms of these core-shell structured single-crystals with nonuniform incorporation will be elucidated in the next chapter.…”
Section: Nonuniform and Patterned Incorporationmentioning
confidence: 99%
“…Very recently, the internal structure of a crystal could be even patterned sequentially with different incorporation states by dynamically oscillating the conditions instead of the traditional uniform incorporation. 28 Meanwhile, mechanisms of the encapsulation of guest materials inside the single-crystals have been discussed frequently within these years. 29,30 In detail, tremendous factors affecting the crystallization have been elucidated to govern the incorporation process, such as crystal growing rate and physical or chemical properties of both guest materials and host crystals.…”
Section: Introductionmentioning
confidence: 99%